ความฉลาดทางอารมณ์ของครูปฐมวัย สำนักงานเขตพื้นที่การศึกษาอ่างทอง สำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน กระทรวงศึกษาธิกา - ฐานมาศ แก้วอนันต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this study was to investigate the level of early childhood teachers’ emotional intelligence, along with related factors. The sample included 216 early childhood teachers at Ang Thong Educational Service Area Office, Office of the Basic Education Commission, Ministry of Education. The instrument are personal and operation questionnaire, emotional intelligence evaluation form, personality test (MPI). Data was analyzed using percentage, mean and standard deviation. The relationship between these variables was discovered using chi-square, unpaired t-test, one-way ANOVA. Relation among personality test as well as Pearson’s correlation test and the remaining predictors of teachers’ high emotional intelligence was analyzed by using multiple logistic regression. The result revealed that mostly of early childhood teachers were female, over 50 years of age, bachelor’s degree education, marriage, with 12.37±9.12 years work experience, having working status of governmental teachers, introversion personality is 51.4%, extraversion personality is 48.6%, stability personality is 58.8%, neuroticism personality is 41.2%. The results revealed that the mean total scores of emotional intelligence and mean scale scores were within the normal range and high normal range in self-control. Related factors of emotional intelligent were income sufficiency (p<0.05), congenital disease (p<0.05), numbers of students (p<0.05), work experience (p<0.05) and teaching contact hours (p<0.05). Scale E personality had a positive significant correlation(r = 0.331) to emotional intelligence (p<0.05). Scale N personality had a negative significant correlation(r = -0.565) to emotional intelligence (p<0.01). Multiple logistic regression showed that the predictors of emotional intelligence level were having sufficient income, teaching 20 or less students, stability emotional personality and extrovert personality.